The Culture of Student Debate: When not to Argue - A. A. Vasilyeva (Концепт: философия, религия, культура, 2022)
Today public speaking as a form of communication calls for the development of actives ways of speaker’s interaction with the audience, with the audience taking on an increasingly active and meaningful participation. In the cultural environment of modern higher education, in universities, student debates are becoming one of the most relevant and popular activities. Basing on the assumption that debate is an effective tool for developing both communicative and speech skills of future professionals in any field of activity focused on social interaction, this study aims to investigate the specifics of the organizing and conducting debates to develop mastery, professionalism, and leader potential of students in the framework of the course of Russian as a second foreign language (RSL). With this approach in mind, we set the following objectives: 1) to clarify the main approaches to the meaning of oral communication and the role of debate in it for the formation of basic competencies of students today; 2) to study the structure of typical units of public speaking; 3) to identify problems students face in the process of verbal communication; 4) to substantiate the advantages of using debates for the development of the necessary general cultural, professional and communicative qualities and skills of a future professional. In its methodology, this study was based on the works in the field of the theory of communication, the language of business communication, the culture of speech, pedagogy, and methods of teaching the Russian language to non-native speakers. The research methods included surveys and interviews, as well as content analysis and case study methods. The study has proved that solving the pedagogical problems of fostering responsibility, independence, and proactive social attitude requires the development of general cultural, research and communication skills, and debates have proved to be an effective form of practicing these skills in the educational process. The communicative culture and the overall training of students for their future professional career means leadership development, and for this cause debates are an effective teaching tool.